Emotions, technology, and digital games - Tettegah, Sharon Y.; Huang, WenHao (Academic Press, is an imprint of Elsevier, 2016)
Emotions, Technology, and Digital Games explores the need for people to experience enjoyment, excitement, anxiety, anger, frustration, and many other emotions. The book provides essential information on why it is necessary to have a greater understanding of the power these emotions have on players, and how they affect players during, and after, a game. This book takes this understanding and shows how it can be used in practical ways, including the design of video games for teaching and learning, creating tools to measure social and emotional development of children, determining how empathy-related thought processes affect ethical decision-making, and examining how the fictional world of game play can influence and shape real-life experiences
Keywords: GAMES / Video & Electronic; Gesellschaft; Psychologie; Electronic games -- Psychological aspects; Video games -- Psychological aspects; Electronic games -- Social aspects; Digital media -- Social aspects; Emotions -- Sociological aspects; Human-computer interaction; Technologie; Gefühl; Computerspiel; Aufsatzsammlung